Servo Control for Missile System. (December 2019) - Nataliana, Decy; Syafruddin, R; Devira Ramady, Givy; Liklikwatil, Yakob; Ghea Mahardika, Andrew
Abstract: The ability to make control systems is very limited, especially high-speed two-dimensional motion controls such as missile controls, for that reason researchers try to examine the title Servo Control For Missile System. As a researcher, his goals and hopes from this simple one can become a prototype, the endurance test and then can be used as mass production. Where the stages of this research method make Servo Control For Missile System, the control signal is received through the radio to be processed. Here the researchers used codevision software to create a software application, the signal from the radio then combined with the optical encoder position signal, to get smoother and more precise motion, stopping at a position that is has been ordered then as feedback is input from the encoder servo motor, then the signal is amplified to drive motor power amplifier driver circuit. In this case, the signal processing uses a microcontroller, with several considerations, including a fairly small physical dimension where the outer diameter of the casing is 120mm, the inner diameter is 116mm. Overall Servo Control For Missile System which is a real-time software and hardware control signal application to drive fin.